CATEGORY SHIFTS AND IMPACT OF TRANSLATION IN “THE SECRET OF UNICORN” MOVIE TEXTS - Andriyani, Seftiy; Widiyantari, Yunita (Surakarta English and Literature Journal, 2020)
This study aims for (1) analyzing the kinds of category shifts found in the movieof The Adventure of Tintin “The Secret of Unicorn” into Indonesian Subtitle, (2)explaining the dominant category, and (3) describing the influences of thosecategory shifts on transferring the messages of the source language. The data inthis research were all of the sentences spoken by the actors in The Adventure ofTintin “The Secret of Unicorn“ movie, whose translations (subtitles) contain anytype of category shifts This research was a descriptive qualitative research. Theprocess of collecting data is by taking all data that are suitable to the criteria andsupported the research. There are four types of category shifts occured in thesubtitling text of the The Adventure of Tintin “The Secret of Unicorn” movie.They are structure shift, class shift, unit shift and intra-system shift. Thestructure shift has the highest frequency, that is 289 cases or about 50.7 %. Theoccurrence of category shift in this movie can make the translation’s result morenatural, accurate, and communicative.